Equity valuation Mercedes-Benz Group AG - Almirante, Tiago (2024)
The automotive industry has been suffering a lot of changes recently. Topics like shared mobility, autonomous driving and electric vehicles came to revolutionize this sector. In an economic environment that is still recovering from the Covid-19 pandemic, the vulnerabilities of this sector came forward. Challenges related to supply chain disruptions, increasing inflation rates and raw materials prices came to enhance the perseverance of the major firms. Mercedes Benz AG, known as one of the most reputable luxury brands in the industry, has been investing to face these changes. Therefore, this dissertation aims to estimate the fair value of Mercedes Benz Group AG share at the end of 2024. This thesis highlights each division of the company, after the spin-off of Daimler AG on 2021, using three main methodologies: Discounted Cash Flow (DCF), Relative Valuation and the Dividend Discount Model (DDM). To present the background of the assumptions taken, an overview of the company, as well as its strategy and ownership structure was made. Additionally, industry overview and key players are presented to showcase the competition faced by the firm. Furthermore, DCF model estimates a fair value of €81,31 for Mercedes-Benz share. Relative valuation returned an average value of €55,39 and the Dividend Discount model led to a share price of €44,92. Thus, this dissertation highlights a HOLD recommendation, based on the attribution of a 10% weight to the DDM, 20% to the Relative Valuation and a 70% weight to the DCF model, reaching a final Share price of €72,48.